The Effect Of Fibrous Concrete Batches At The Age Of 730-Days Through Analytical And Experimental Tests - Indradi Widjatmiko; Ari Wibowo; Devi Nuralinah; D. Mulyaningrum (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
This research is a continuous study to investigate the effect of fibrous concrete batches at the age of 730-days and hence makes a comparison with experimental results conducted by Bryceson (2003). Modelling the finite element is carried out in linear static solver and non-linear static solver to verify the experimental results of column specimens recorded by Bryceson (2003). Polypropylene fibres were used in this study with the high strength concrete of recorded compressive strength of 72 MPa (Bryceson, 2003). Two fibre contents (0.1 %, and 0.3 %) with different fibre location were proposed by Bryceson (2003) for the column specimens. For each batch of fibre content, three columns were cast by Bryceson (2003). One consisted of fibrous concrete for the entire section, while the second column consisted of fibrous concrete at the cover and the region through the steel reinforcement only and the third column consisted of fibrous concrete at the cover only. A control references column was cast with non-fibrous concrete at the entire cross-section for comparison purpose (Bryceson, 2003). Therefore, in this study, similar modelling of columns was done in finite element analysis to conduct the analytical results. All column models were tested in finite element analyses in both linear static solver and non-linear static solver under concentric axial compression. Linear static solver used the ultimate load which was recorded by Bryceson (2003) to determine the displacement, while the non-linear static solver used ultimate load with increment (0%, 20%, 40%, 60%, 80%, and 100%). The analytical results are then graphed and compared with the experimental results which were conducted by Bryceson (2003). This study found that the analytical results obtained from non-linear static solver provides a better comparison for the experimental results conducted by Bryceson (2003) as compared to analytical results obtained from linear static solver. This study found that the column of 0.1% fibre content at the cover produced the least displacement of 11.19 mm in non-linear static solver compared to others. In conclusion, 0.1 % fibre content exhibited a better performance in terms of lower displacement.